OPTIMALISASI PENGGUNAAN KALIMAT EFEKTIF DALAM PENULISAN YANG SESUAI KAIDAH BAHASA INDONESIA - Alawiyah, Tuti; Juniarti, Restia Nanda; Syuhada, Irfan; Arraziq, Muhammad Erai; Mubarok, Ismail (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The use of effective sentences is very important in formal and academic communication because it can affect the understanding and quality of the message conveyed. However, there are still many errors found in the use of ineffective sentences, which reduces the clarity and accuracy of the writing. Therefore, this study aims to identify and provide guidance on optimizing the use of effective sentences in accordance with Indonesian rules. The method used in this study is a literature review, by analyzing various literature related to effective sentences, Indonesian language rules, and appropriate writing guidelines. The results of the study show that the application of effective sentences in formal and academic writing can improve the quality of communication and reader comprehension. The discussion reveals various principles of effective sentences, such as clarity, frugality, unity, and logic, which must be applied in every writing. In addition, the importance of understanding and applying Indonesian rules in maintaining accuracy and professionalism in writing was also found. In conclusion, optimizing the use of effective sentences based on Indonesian rules is very important to produce quality, clear, and easy-to-understand writing, so that it can improve the quality of written communication in various contexts, especially in academic and professional environments